Aplikasi Kehadiran Mahasiswa Menggunakan NFC Card Berbasis Mobile Android - Maulana Anas Jaffar; Purwantoro Purwantoro; Azhari Ali Ridha (Teknik Informatika Universitas Pamulang, 2021)
Various kinds of activities in the fields of communication, information, transportation, banking, education, and those that require high mobility, require a supporting technology to do so. The supporting technology is a smartphone, where this smartphone is almost owned by every level of society. Smartphones are widely used in education to support learning between lecturers and students. At the University of Singaperbangsa Karawang Faculty of Computer Science, there is one aspect of student assessment that is measured based on the number of students pre-sent. The attendance system that runs at the Singaperbangsa University of Karawang, Faculty of Computer Science, has not yet implemented smartphone technology in its implementation. The problems that arise with the attendance system at this time is the presence data that has no backup if lost and absenteeism records that are easily damaged. Therefore the design and manufacture of the NFC Presence application is carried out to overcome this problem. The NFC Pres-ence application was built using the Mobile Application Development Life Cycle (MADLC) method. NFC (Near Field Communication) on smartphones and NFC Card is a tool to support student attendance data, which will then be stored properly in the database to prevent student attendance data loss. The attendance pro-cess in the NFC Presence application is done by mentoring an NFC card containing data in accordance with the data-base to the lecturer smartphone. Furthermore, the lecturer smartphone will send attendance data to the database, so that this data can be accessed anytime, anywhere.